Childhood Systemic Lupus Erythematosus; A Rare Multisystem Life-threatening Disorder: a case of 13 years-old-girl with oral involvement and joint pain as primary clinical manifestation (Journal of Pharmaceutical Negative Results, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune illness that affects several organs, and the most frequent renal consequence of SLE is lupus nephritis (LN). It is a rare, systemic disease, possibly fatal autoimmune illness with high morbidity. SLE prevalence has been observed to range between 14 and 60 per 100,000 people. A 13-year-female child was admitted to the hospital in the paediatric ward with the chief complaint of skin lesion over sun sun-exposed and bleeding from oral mucosa. Blood samples were sent to the laboratory for investigations, and blood cultures were also sent to the microbiology lab. As soon as she was admitted, treatment was started without any delay. Blood investigations show a decreased level of WBC count, i.e. 3500 cu/mm, and the blood culture revealed the organism's growth. Hence patient was started on injectable antibiotics. After 15 days of a continuous course of antibiotics, the patient started recovery. The rashes started disappearing a little bit. Physiotherapy is begun for a child with joint pain where she experiences relief.